(untitled) (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2024)
The literature review examines interpersonal communication between nurses and patients, focusing on how communication methods, forms, and skills influence patient satisfaction with the care received. Various research exploring the importance of effective communication in the health care setting is highlighted, underscoring its impact on the patient’s perception of the quality of care and their overall well-being. The findings highlight the need for nurses to develop empathetic, clear, and effective communication skills to establish trusting relationships with patients, which can improve treatment adherence, reduce anxiety, and promote positive health outcomes. This review underscores the relevance of investing in the development of interpersonal communication skills in the nursing setting to improve the patient experience and quality of care.